The Effect of Anxiety on Students’ Numeracy Score: A Case Study of PISA 2022 - Katon Ramadhan; Muh Amin S (Lembaga Penelitian dan Pendidikan Mandala, 2026)
PISA is a triennial international assessment administered to 15-year-old students from countries participating in the OECD. It measures students’ reading literacy, mathematics (numeracy), and science competencies. In addition to academic achievement, PISA also assesses various contextual factors at both the school and student levels that may influence student performance. One psychological factor measured in PISA that may affect students’ numeracy outcomes is anxiety. This study aims to analyze the effect of anxiety on Indonesian students’ numeracy achievement. A simple linear regression model was employed to explain the nature of this effect. The results indicate that anxiety has a statistically significant negative effect on numeracy achievement. However, this factor explains only a small proportion of the variance in students’ numeracy outcomes.